Analisa Hubungan Antara Intensitas Persaingan, Ukuran Perusahaan, Organisasi Pembelajaran dengan Penggunaan Sistem Informasi Akuntansi Pada Sektor Ritel di Surabaya - Felycia Eri (Business Accounting Review, 2013)
Retail sector made the largest contribution to Gross Regional Domestic Product of Surabaya City in 2011, with a donation of 29.71%. The growth in the number of retail firms in Surabaya is also increasing every year. To be able to survive in competition, the management must be able to perform the right decision. The appropriate decisions based on the accurate, relevant, timely information that can be produced through Accounting Information System (AIS). By realizing the importance of AIS usage at retail sector, therefore researcher interested in doing research that aimed to know the relationship between competitiveness intensity, firm size, learning organization and the usage of AIS. The data were collected by distributing questionnaires to the owners or managers (15 food retailers and 90 general merchandise retailers) in Surabaya. Statistical analysis used in this research was Pearson Product Moment Correlation Analysis. This research was able to prove the existence of positive and significant correlation between the competitiveness intensity with the usage of AIS; firm size with the usage of AIS; and learning organization with the usage of AIS. Most of the usage of AIS at retail sector actually more emphasis on Financial Reporting System aspect which for fulfilling of responsibility to external parties such as providing financial statements to the owner.